2023
DOI: 10.3389/fmech.2023.1204893
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and energy absorption properties of 3D-printed honeycomb structures with Voronoi tessellations

Abstract: 3D printing technology is the new frontier in building construction. It is especially useful for making small structures within a short period. Full construction, including interior partitions and exterior façades, can be achieved with this technology. This paper proposes a parametric Voronoi tessellations model for quickly generating and fabricating 3D-printed hexagonal honeycomb partitions for interior design. Comprehensive experimental testing was conducted to characterize the mechanical properties and inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…By using a collapsible and sturdy aluminum frame and an isolated XZ actuator system to protect electrical connections and dynamic components, the 3D printer could be easily deployed off-grid to help in providing assistance by quickly fabricating tools and equipment (Figure 20a). [61], (e) an optimized 3D-printed honeycomb structure [64], (f) a concrete 3D-printed prestressed bridge [65], (g) Wire-and-Arc manufactured pillars [66], and (h) a 3D-printed formwork to realize a thin shell structure [67].…”
Section: Design By 3d-printing Of Construction Componentsmentioning
confidence: 99%
See 4 more Smart Citations
“…By using a collapsible and sturdy aluminum frame and an isolated XZ actuator system to protect electrical connections and dynamic components, the 3D printer could be easily deployed off-grid to help in providing assistance by quickly fabricating tools and equipment (Figure 20a). [61], (e) an optimized 3D-printed honeycomb structure [64], (f) a concrete 3D-printed prestressed bridge [65], (g) Wire-and-Arc manufactured pillars [66], and (h) a 3D-printed formwork to realize a thin shell structure [67].…”
Section: Design By 3d-printing Of Construction Componentsmentioning
confidence: 99%
“…The compression tests demonstrated that the application of the low-modulus stiffeners increased the ultimate bearing load more than four times, altering the deformation behavior of the specimens, and that further studies should be carried out on developing a reliable adhesive connection between the aluminum profile and polymeric stiffeners. Lastly, in [54], the authors proposed the use of [51], (b) a lightweight concrete 3Dprinted module [56], (c) a prefabricated concrete 3D-printed module [60], (d) a closed-cell lightweight concrete 3D-printed wall module [61], (e) an optimized 3D-printed honeycomb structure [64], (f) a concrete 3D-printed prestressed bridge [65], (g) Wire-and-Arc manufactured pillars [66], and (h) a 3D-printed formwork to realize a thin shell structure [67].…”
Section: Design By 3d-printing Of Construction Componentsmentioning
confidence: 99%
See 3 more Smart Citations